Effect of Sleep Quality and Duration on Jitter, Shimmer, and Harmonics-to-Noise Ratio among Colombian University Professors - Rincón Pinilla, María Paula; Carrillo-González, Andrés; Cantor-Cutiva, Lady Catherine (Revista Chilena de Fonoaudiología, 2023)
Professors who sleep 6 or fewer hours are more likely to report voice symptoms. However, only three studies have been published on this topic, basing their conclusions on self-reported surveys and displaying an overall weak methodological quality, which hinders the generalization of these results. This exploratory, correlational, and longitudinal study aimed to determine the association between sleep quality and duration and three acoustic parameters linked to voice harmonicity and quality (jitter, shimmer, and Harmonics-to-Noise Ratio [HNR]) among 24 Colombian university professors. Generalized linear models with gamma distribution were used to analyze this association. Our results indicate that the professors who reported good sleep quality had significantly lower HNR values compared with those who had a low sleep quality. Additionally, increased jitter (B= 0.10) and shimmer (B= 0.10), and decreased HNR (B= -0.05) values were found when the duration of sleep increased. In contrast, participants with good self-perceived sleep quality and a shorter sleep duration presented lower voice harmonicity compared to those with bad sleep quality and shorter sleep duration, which may be associated with the physiological and emotional effects of sleep on voice production. Considering the multifactorial nature of voice production and the exploratory nature of the present study, it is important to note that a statistically significant correlation between sleep quality and duration and voice harmonicity does not necessarily imply that sleep directly causes voice disorders, but rather suggests that sleep is a variable to be considered when analyzing and treating individuals with voice issues. These findings provide insight into the complex interplay of variables that may contribute to voice disorders and highlight the importance of considering sleep as a potential contributing factor in the assessment and management of individuals with voice issues.